PEMANFATAN TUMBUHAN SEBAGAI BAHAN RUM-RUMEN (MINUMAN KESEHATAN ETNIS KARO) OLEH PEDAGANG TUMBUHAN OBAT DI PASAR PANCUR BATU SUMATERA UTARA - Silalahi, Marina (Universitas Tribhuwana Tunggadewi, 2020)
Written documentation of local knowledge about health drinks, especially the Karo ethnic group, is still limited, although degradation is accelerating with the introduction of information technology. This study aims to determine the diversity of rum-rumen plants, their properties and bioactivity. The method used in the survey and in-depth interviews of 11 traders of medicinal plants is used as a material for making rum-rumen and their benefits. Respondents in this study were all traders of medicinal plants in the Pancurbatu market who traded rum- rumen material. The data obtained were analyzed qualitatively and descriptively. The results showed that the rum-rumen is a health drink derived from extracts of 6 plant species originating from 3 families. Leaves and stems are the most widely used organs. The benefits of rum rumen are blood circulation, overcoming headaches, overcoming digestive tract disorders, treating cholesterol and also anti-hypertension. The conclusion that all types of plants used as ruminal ingredients are rich in essential oils. The three plants are Ocimum basilicum, Plectranthus amboinicus and Cymbopogon citratus as the main ingredient of rumen have bioactivity as antimicrobial and anti-cancer especially microbes that infect the digestive and respiratory tract. Rum-rumem drink is very potential to be developed into a health drink to treat digestive and respiratory disorders.